Trends and characteristics of AIDS mortality in the Rio de Janeiro city after the introduction of highly active antiretroviral therapy - Valéria Saraceni; Marly Marques da Cruz; Lilian de Mello Lauria; Betina Durovni (Brazilian Journal of Infectious Diseases)
We examined the characteristics of AIDS mortality in Rio de Janeiro city from 1995 to 2003. During this period, highly active antiretroviral therapy with protease inhibitors was made available, and it changed the pattern of the epidemics. There was a 47.5% reduction in the number of AIDS deaths within the period, with an increase in the proportion of women among the deceased; their schooling was lower than that of the men, similar to the trends of the national-level epidemics. The main place of death changed from university hospitals to emergency rooms. The proportion of cases reported to the National Diseases Surveillance System (SINAN) reported only through the death certificate remained high. Although there is free distribution of antiretrovirals by the public health system, many patients still lack access to diagnosis and treatment. We need to give priority to access to anti-HIV testing and treatment, to increase the quality of care and to look into the issue of adherence in order to further reduce AIDS mortality.